Trends in female genital mutilation (FGM) among Senegalese women and their daughters : a secondary analysis of Senegal DHS from 2015 to 2023 - Ndeye Mareme Sougou; Mouhamadou Faly Ba; Fatou Bintou Diongue; Amadou Ibra Diallo; Ibrahima Ndiaye; Ibrahima Seck (BMC Public Health)
Abstract Background Female genital mutilation (FGM) is a deeply rooted practice in Senegal, generally affecting girls at a very young age. The prevalence of FGM has remained virtually unchanged for at least two decades. The aim of this study is to identify the factors associated with the evolution of this practice in Senegal. Methods This study is a secondary analysis of data extracted from the Senegalese Demographic and Health Surveys (DHS) from 2015 to 2023. The record individual file of women aged 15 to 49 was used for the analysis. For both women aged 15-49 and their daughters, the dependent variable was "being circumcised". This is a binary qualitative variable which was coded as"Yes" if the woman and/or her daughter had been circumcised. A descriptive analysis was performed. A multivariate analysis was performed to determine the Adjusted Odds Ratios (ORaj) and estimate the corresponding 95% confidence intervals (CI) for all variables. Adjustment was made on a yearly basis. Results The prevalence of female circumcision was 24.2% in 2015, 22.7% in 2016, 24.0% in 2017, 23.3% in 2018, 25.2% in 2019 and 20.1% in 2023. The majority of women who undergo FGM do so between the ages of 0 and 9. The most frequent form of mutilation is "flesh removed from genital area", the frequency of which rises from 58.3% in 2015 to 76.5% of cases of mutilation in 2023. Infibulation (genital area sewn closed), which was the least common form of mutilation at 7% in 2015, will increase to 25.6% in 2023. The factors associated with the development of FGM among Senegalese women were region of residence and socio-economic level. Conclusion Our study has shown that the fact that the mother has been circumcised is a risk factor for the daughter. However, the level of wealth and education of women and their husbands would appear to be protective factors against the development of FGM in girls. To bend the curve, political decision-makers need to take targeted action in hotspot regions, considering aspects linked to women's empowerment.